2021
DOI: 10.1101/2021.06.11.448153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A panel of KSHV mutants in the polycistronic kaposin locus for precise analysis of individual protein products

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is the infectious cause of several human cancers including the endothelial cell (EC) malignancy, Kaposi's sarcoma. Unique KSHV genes absent from other human herpesvirus genomes, known as K-genes, are typically important for KSHV replication and pathogenesis. Among the K-genes, the kaposin mRNA is highly expressed in both latent and lytic phases of infection, but its polycistronic nature has hindered methodical analysis of the role of kaposin translation products i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…In our previous work, we showed that KSHV infection induced PB disassembly (52) and more recently we confirmed that KapB was not only sufficient but also necessary for this effect with the delB BAC16 virus (93). To determine if autophagic machinery is also required for PB disassembly in the context of KSHV infection, we silenced Atg5 or NDP52 in HUVECs prior to infecting with rKSHV.219 for 96 hours to establish latency, then stained for PBs.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…In our previous work, we showed that KSHV infection induced PB disassembly (52) and more recently we confirmed that KapB was not only sufficient but also necessary for this effect with the delB BAC16 virus (93). To determine if autophagic machinery is also required for PB disassembly in the context of KSHV infection, we silenced Atg5 or NDP52 in HUVECs prior to infecting with rKSHV.219 for 96 hours to establish latency, then stained for PBs.…”
Section: Resultsmentioning
confidence: 55%
“…In parallel, we immunoblotted infected cell lysates and observed that KSHV increased phosphorylation of Ser90 of Beclin 1 (Fig 7B), consistent with earlier observations of Ser90 phosphorylation after ectopic expression of KapB (Fig 3D). To confirm if KapB was necessary for upregulated autophagic flux after KSHV infection, we used a recombinant KSHV that does not express KapB (delB BAC16) and matched wild-type control (BAC16 KSHV), described in our recent publication (93). We infected HUVECs with WT BAC16 KSHV or delB BAC16 virus for 96 hours to permit latency establishment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel, we immunoblotted infected cell lysates and observed that KSHV increased phosphorylation of Ser90 of Beclin ( Fig 7B ), consistent with earlier observations of Ser90 phosphorylation after ectopic expression of KapB ( Fig 3D ). To confirm if KapB was necessary for upregulated autophagic flux after KSHV infection, we used a recombinant KSHV that does not express KapB (delB BAC16) and matched wild-type control (BAC16 KSHV), described in [ 102 ]. We infected HUVECs with WT BAC16 KSHV or delB BAC16 virus for 96 hours to permit latency establishment.…”
Section: Resultsmentioning
confidence: 99%